Regulation of PI-3-Kinase and Akt Signaling in T Lymphocytes and Other Cells by TNFR Family Molecules - So, Takanori; Croft, Michael (Frontiers in Immunology, 2013)
Activation of phosphoinositide 3-kinase (PI3K) and Akt (protein kinase B) is a common response triggered by a range of membrane-bound receptors on many cell types. In T lymphocytes, the PI3K-Akt pathway promotes clonal expansion, differentiation, and survival of effector cells and suppresses the generation of regulatory T cells. PI3K activation is tightly controlled by signals through the T cell receptor (TCR) and the co-stimulatory receptor CD28, however sustained and periodic signals from additional co-receptors are now being recognized as critical contributors to the activation of this pathway. Accumulating evidence suggests that many members of the Tumor Necrosis Factor receptor (TNFR) superfamily, TNFR2 (TNFRSF1B), OX40 (TNFRSF4), 4-1BB (TNFRSF9), HVEM (TNFRSF14), and DR3 (TNFRSF25), that are constitutive or inducible on T cells, can directly or indirectly promote activity in the PI3K-Akt pathway. We discuss recent data which suggests that ligation of one TNFR family molecule organizes a signalosome, via TNFR-associated factor (TRAF) adapter proteins in T cell membrane lipid microdomains, that results in the subsequent accumulation of highly concentrated depots of PI3K and Akt in close proximity to TCR signaling units. We propose this may be a generalizable mechanism applicable to other TNFR family molecules that will result in a quantitative contribution of these signalosomes to enhancing and sustaining PI3K and Akt activation triggered by the TCR. We also review data that other TNFR molecules, such as CD40 (TNFRSF5), RANK (TNFRSF11A), FN14 (TNFRSF12A), TACI (TNFRSF13B), BAFFR (TNFRSF13C), and NGFR (TNFRSF16), contribute to the activation of this pathway in diverse cell types through a similar ability to recruit PI3K or Akt into their signaling complexes.